REPRODUCTIVE PERFORMANCE OF NILI-RAVI BUFFALOES IN AZAD KASHMIR, - Z. Hussain; K. Javed S.M.I. Hussainn; G. S. Kiyani (Journal of Animal and Plant Sciences, 2006)
A total of 376 Performance records of 109 Nili-Ravi buffaloes maintained at Livestock Development Research Centre, Raroo, Muzaffarabad, Azad Kashmir, during 1989-2003 were utilized for the evaluation of some non-genetic factors affecting age at first calving, post partum oestrus interval, service period and calving interval. The Least squares means for age at first calving, post-partum oestrus interval, service period, and calving interval were 1644.87+36.31 days, 157.4+22.03 days, 208.35+24.03 days and 473.72+3.56 days respectively. A non-significant effect of season of birth on age at first calving was observed, while the effect of year of birth on age at first calving was significant (P<0.01). Post-partum oestrus interval was found to be significantly (P<0.01) influenced by season and year of calving, while a non-significant effect of both season and year of calving was observed on service period and calving interval. Parity had a significant (P<0.01) effect on post-partum oestrus interval and calving interval, while a non-significant effect of parity was observed on service period during the study.
Keywords: Nili-Ravi buffaloes; Azad Kashmir; reproductive performance